Digital Literacy and Digital Financial Literacy Enhancement Program for Karang Taruna members : Program Peningkatan Literasi Digital dan Literasi keuangan Digital bagi Anggota Karang Taruna - Setyawan, Hendri; Suhendi, Chrisna (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The "Enhancing Digital Literacy and Digital Financial Literacy" program is highly relevant due to the increasing use of the internet and digital financial transactions. It is essential for community members to understand online ethics and financial security. This program targets members of the Karang Taruna RT 2 RW 3, Mangunharjo Village, Tembalang District, Semarang City. Activities include seminars and interactive discussions. The program aims to improve digital literacy and digital financial literacy among Karang Taruna RT 2 RW 3 members, Mangunharjo. Through seminars and interactive discussions, participants' understanding of internet ethics, digital security, and digital financial management improved by 87%. This program highlights the importance of continuous education in building resilient communities capable of facing the ever-evolving digital challenges